2021
DOI: 10.1111/ssm.12452
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of digital mathematics games based on the NCTM Content and Process Standards: An exploratory study

Abstract: This exploratory study was conducted to evaluate the quality of digital math games by measuring how much the content of a digital game is aligned to the NCTM Content and Process Standards. For this purpose, this study employed a content analysis method. In total, 23 digital mathematics games have been selected and analyzed using an instrument, a codebook, developed from the NCTM Content and Process Standards. The data showed that a variety of game genre have been used in mathematics games. The majority of math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…While 61% of the studies include between 1 and 5 games (Es-Sajjade & Paas, 2020; Koneva & Shabanova, 2021), a significant percentage of the content of the games belongs to the "numbers and operations" learning area (Eyster, 2017;Galarza, 2019;Wouters & Van Der Meulen, 2020). In the research conducted by Joung and Byun (2020), in which digital mathematics games were analysed according to National Council of Teachers of Mathematics [NCTM] standards, it was determined that the majority of the games were related to the "numbers and operations" learning area. However, very few games were prepared for the "data", "statistics" and "probability" learning areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While 61% of the studies include between 1 and 5 games (Es-Sajjade & Paas, 2020; Koneva & Shabanova, 2021), a significant percentage of the content of the games belongs to the "numbers and operations" learning area (Eyster, 2017;Galarza, 2019;Wouters & Van Der Meulen, 2020). In the research conducted by Joung and Byun (2020), in which digital mathematics games were analysed according to National Council of Teachers of Mathematics [NCTM] standards, it was determined that the majority of the games were related to the "numbers and operations" learning area. However, very few games were prepared for the "data", "statistics" and "probability" learning areas.…”
Section: Discussionmentioning
confidence: 99%
“…When examining the studies that use the method of teaching with games, it was found that teaching with games increases academic achievement (Liang, Zhang, Long, Deng & Liu, 2019;Rawansyah, Pramudhita & Pramitarini, 2021;Rondina & Roble, 2019) and positively affects attitudes toward mathemati cs instruction (Chiang & Qin, 2018;Tuekle, 2020), and that research participants positively evaluate the use of games in mathematics instruction (Bragg, 2007;Koç-Deniz, 2019;Russo, Bragg & Russo, 2021;Watson-Huggins, 2018).Along with the increase in studies conducted on teaching mathematics with games in recent years, compilation studies are also encountered (Divjak & Tomić, 2011;Joung & Byun, 2020;Türker & Arslan, 2021). Divjak and Tomić (2011) analyzed 32 studies conducted between 1995 and 2010, in which an attempt was made to determine the effect of games on motivation and achievement of learning goals in mathematics education through the use of mathematical computer games.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, many teachers perceive the use of technology to be for presentation and the integration of mathematics and technology to equate to playing games on the computer. A practice Joung & Byun (2021) posit should consider the extent to which the content aligns with the NCTM Content and Process standards, noting most focus on the development of Number and Operations.…”
Section: Theoretical Frameworkmentioning
confidence: 99%